Characterization of Prepractice Injury Prevention Exercises of High School Athletic Teams. (November 2017) - Slauterbeck, James R.; Reilly, Autumn; Vacek, Pamela M.; Choquette, Rebecca; Tourville, Timothy W.; Mandelbaum, Bert; Johnson, Robert J.; Beynnon, Bruce D.
Background: Static and dynamic exercises are performed before activity to decrease injury risk and increase performance. Although evidence supports using dynamic over static stretching and performing Fédération Internationale de Football Association (FIFA) 11+ as a dynamic prepractice routine, we do not know the frequency at which these exercises are utilized in high school populations. Hypothesis: We hypothesize that there is a wide variety of preparticipation exercises performed by high school athletes, and that few high school teams perform FIFA 11+ as an injury prevention program in its entirety. Study Design: Observational study. Level of Evidence: Level 4. Methods: High school prepractice routines were observed for 185 teams (football, soccer, basketball, and lacrosse) over 1 season. The percentages of team warm-up routines that included components of FIFA 11+ were calculated, and the chi-square test was used to compare sex, sport, and level of competition. Results: Of a total 644 warm-up observations, 450 (69.9%) included only non–FIFA 11+ exercises, 56 (8.7%) included at least 1 FIFA 11+ exercise, and 38 (5.9%) included only jogging; 69 (10.6%) consisted only of sport-specific activities. The type of warm-up differed significantly between males and females ( P = 0.002), sports ( P < 0.001), and level of competition ( P < 0.001). Static stretching and athletes stretching on their own were observed in 14% and 15% of all observations. No team performed the FIFA 11+ injury prevention routine in its entirety. Conclusion: The type of warm-up differed by sex, sport, and level of competition. Static stretching was performed more frequently than anticipated, and an entire FIFA 11+ warm-up was never performed. Clinical Relevance: We need to identify the exercises that decrease injury and increase performance and better inform the athletic population about the risks and benefits of static and dynamic warm-up programs.